La iportancia de los stakeholders de la organización: Un análisis empírico aplicado a la empleabilidad del alumnadeo de la universidad espa\~nola - G. Caballero Fernández; J. M. García Vázquez; M. A. Quintás Corredoira (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2007)
This work has the intention of meeting the stakeholders of the organization and, in particular, the importance perceived by the manager of each of them. After a review of the literature, we analyze diverse qualities of the stakeholders that influence the importance that is granted to them. Our results applied to the employability of the pupils of the spanish university, allow us to emphasize qualities of each of the different stakeholders as the power that they possess to influence the public image of the center and the skill to keep on showing his worries on the employability in a future.
Keywords: 330; attributes of the stakeholders; importance of the stakeholders; employability of the graduates